Preferred Site Selection Using GIS and AHP: Case Study in Bangka Island NPP Site - Ari Nugroho; Eko Kusratmoko; Tito L. Indra (Jurnal Pengembangan Energi Nuklir, 2021)
PREFERRED SITE SELECTION USING GIS AND AHP: CASE STUDY IN BANGKA ISLAND NPP SITE. Industrial growth affects the increasing demand for electricity in various places, this also occurs on the island of Bangka. So far, electricity supply has only been obtained from fossil fuel power plants with inadequate capacity, unstable flow and depending on fuel supplies from outside the island. For this reason, it is necessary to build a Nuclear Power Plant (PLTN) which is believed to be reliable and able to overcome these problems. In order to prepare a safe and economical nuclear power plant site, influential parameters such as population density, cooling system, land clearing, cut and fill, and granite for the foundation have been analyzed. The novelty of this analysis lies in 2 methods which gradually used before come up with a final decision, namely spatial analysis and pairwise comparison using Geographic Information Systems (GIS) and Analytical Hierarchy Process (AHP), respectively. The scope of study area is based on the site vicinity (1:5.000) scale, located in the districts of West and South Bangka. The siting process refers to the rules set by the International Atomic Energy Agency (IAEA). Based on the final results of the analysis using the expert choice program, the numerical weights for West Bangka and South Bangka were 0.709 and 0.291, respectively, with a consistency value of 0.03.